1471. Case Report: Andes Virus Hantavirus Pulmonary Syndrome in a Traveler Returning to the United States. (26th November 2018) - Bergamo, David; Bacon, Alfred; Cohen, David; Eggers, Paula; Kofman, Aaron; Choi, Mary; Klena, John
Abstract: Background: Andes virus (ANDV), a New World hantavirus, is transmitted to humans via contact with the long-tailed pygmy rice rat ( Oligoryzomys longicaudatus ) in Chile and Argentina. Unlike other hantaviruses, ANDV can be transmitted person-to-person. It has a case mortality rate of approximately 30%. Here we describe the first known, imported case of ANDV to the United States. Methods: On January 9, 2018, a 29-year-old female with no significant past medical history returned to the United States from a 3-week group trip to Chile and Argentina. She did not receive vaccines or take prophylaxis. She visited Central California before returning to Delaware. January 19 she presented with fevers, vomiting, and extreme fatigue. Examination was remarkable for hypotension requiring fluid resuscitation and O2 saturation of 89% on room air. She described chest tightness. Influenza, community acquired pneumonia, and PE were considered. Sputum influenza A/B and RSV PCR were negative. Laboratories revealed hypoalbuminemia at 2.2 g/dL, thrombocytopenia at 61, 000, and transaminitis with AST 342 and ALT 302. WBC was within normal range with maximum of 11, 000. Computerized tomography (CT) of chest revealed bilateral lower lobe ground-glass opacities, pleural effusions, and pulmonary edema. She was started on antibiotics. Her symptoms continued. She developed blurred vision and peri-orbital edema. She required 3 L O2 nasal cannula. Headaches, sweats, peripheral edema, and rales developed. Lyme, Ehrlichia, malaria studies, and blood cultures were negative. Acute EBV, CMV, HIV, hepatitis, and dengue serologies were also negative. Hantavirus serologies were obtained Day 4 of admission. She was discharged Day 6 after resolution of fever, hypoxia and thrombocytopenia. Results: Hantavirus ELISA IgG and IgM were reported positive 4 days after discharge and testing at the CDC confirmed ANDV infection. Conclusion: Hantavirus is prevalent in certain South American locales. It should be considered in all patients returning from Chile and Argentina with fever, shortness of breath, and thrombocytopenia. Early recognition of symptoms and hallmark laboratories can identify patients that may require advanced supportive measures to decrease overall mortality. Disclosures: All authors: No reported disclosures.